Analisis Penerapan Siklus PDCA dalam Pengendalian Kualitas Produk Tappet di Industri Komponen Otomotif - Wiyatno, Tri Ngudi; Roni, Dede; Bulqis, Elaeys Mulia; Muyasar, Athariq Dias (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
NT is a Japanese automotive components company that produces automotive products tappet. The quality problem found was the high level ofdefect which was produced in August to October 2024, there were a total of unitsdefect what happened was 4826 units, of the total the type defect dakon chomen became the most dominant, recorded at 2743 units or 57% of the total defect. Therefore, this research is focused on the analysis of the types of defects in dakon chomen. The research method uses the PDCA cycle supported by seven tools (Pareto diagram and fishbone) and 5W1H analysis. Stages plan determine the problem, defect what will be fixed and the causal factors defect, stages do determine the proposed improvements that must be made, the stage check carry out monitoring after carrying out repairs and stages action standardization to maintain product quality. Based on the results of the implementation of the PDCA method, it shows that the number of types defect dakon chomen successfully reduced significantly from 2743 to 1244 units in the period November 2024 to January 2025. This reduction is equivalent to an improvement effectiveness of 55.3%. Keywords: Defect, PDCA, Quality Control, Tappet